2015
DOI: 10.1039/c5ib00071h
|View full text |Cite
|
Sign up to set email alerts
|

MicroC3: an ex vivo microfluidic cis-coculture assay to test chemosensitivity and resistance of patient multiple myeloma cells

Abstract: Chemosensitivity and resistance assays (CSRAs) aim to direct therapy based upon ex vivo response of patient tumor cells to chemotherapeutic drugs. However, successful CSRAs have yet to be developed. Here, we exposed primary CD138+ multiple myeloma (MM) cells to bortezomib, a clinical proteasome inhibitor, in microfluidic-cis-coculture (MicroC3) incorporating patient’s own CD138− tumor-companion mononuclear cells to integrate some of the patients’ own tumor microenvironment components in CSRA design. Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 82 publications
1
49
0
Order By: Relevance
“…Several groups incorporated patient stromal cells into a variety of personalized in vitro platform architectures (K. U. Kim et al, 2005; Pak et al, 2015; Ruppen et al, 2015; Z. Xu, et al, 2013; Young, et al, 2012).…”
Section: The Current State Of Primary Cell Based In Vitro Models: mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups incorporated patient stromal cells into a variety of personalized in vitro platform architectures (K. U. Kim et al, 2005; Pak et al, 2015; Ruppen et al, 2015; Z. Xu, et al, 2013; Young, et al, 2012).…”
Section: The Current State Of Primary Cell Based In Vitro Models: mentioning
confidence: 99%
“…Xu, et al, 2013; Young, et al, 2012). In four cases that assessed the influence of stromal cells on drug sensitivity, the authors found differences in the effective dose of primary cancer cells cultured in a monoculture compared to co-culture, highlighting the importance of integrating supportive cell types into predictive models (Pak, et al, 2015; Ruppen, et al, 2015; Z. Xu, et al, 2013; Young, et al, 2012).…”
Section: The Current State Of Primary Cell Based In Vitro Models: mentioning
confidence: 99%
“…The problem of insufficient cell material available for DSRT can be solved by using miniaturized platforms based on technologies alternative to microtiter plates. There are numerous studies demonstrating utilization of such platforms for screening of live mammalian cells, however few of them are focused on screening of patient‐derived cells with a goal of defining appropriate therapy for cancer patients . Some examples of such studies are given below and summarized in Table .…”
Section: Miniaturized Systems For Dsrt On 2d Cell Culture Modelsmentioning
confidence: 99%
“…Different leukemic cells also indicated different degrees of angiogenic induction, potentially because of the different amounts of angiogenic factors produced, and the sprouted endothelial cells were observed to form lumen structures, both of which could be further enhanced by co-culturing the leukemic cells with the stromal cells. In another study, bone marrow plasma cells from patients with myeloma were cultured on a microfluidic platform; chemosensitivity and resistance assays were carried out to evaluate the ex vivo responses of these primary CD138 + multiple myeloma cells to bortezomib-containing therapies [55]. …”
Section: Modeling Cancer Biology and Physiology In Vitromentioning
confidence: 99%